Solid earth (Copernicus Publ., 2010)
"Solid Earth (SE) is an international scientific journal dedicated to the publication and discussion of multidisciplinary research on the composition, structure and dynamics of the Earth from the surface to the deep interior at all spatial and temporal scales."